2016
DOI: 10.3389/fpsyg.2016.01410
|View full text |Cite
|
Sign up to set email alerts
|

Stress at School? A Qualitative Study on Illegitimate Tasks during Teacher Training

Abstract: What do I expect when stating that “I am going to be a teacher”? Social roles, including professional roles, often become part of people's identity and thus, of the self. As people typically strive for maintaining a positive sense of self, threats to one's role identity are likely to induce stress. In line with these considerations, Semmer et al. recently (e.g., Semmer et al., 2007, 2015) introduced “illegitimate tasks” as a new concept of stressors. Illegitimate tasks, which are defined as unnecessary or unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
0
26
0
2
Order By: Relevance
“…Palmer et al reported effects on disturbed sleep by a lack of support from colleagues28 ) . Whereas the supervisor might be specifically important during teacher training, support by the supervisor might be less important for fully trained teachers2 ) . Future studies should account for social support by colleagues as effects might be different.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Palmer et al reported effects on disturbed sleep by a lack of support from colleagues28 ) . Whereas the supervisor might be specifically important during teacher training, support by the supervisor might be less important for fully trained teachers2 ) . Future studies should account for social support by colleagues as effects might be different.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent longitudinal cohort study of 4,988 Finnish teachers, Gluschkoff and colleagues found workplace violence (as a direct adverse social job characteristic) to disturb sleep – especially, if teachers perceived the managerial practices to be less fair 35 . Schoolmaster training in resource-oriented leadership should add to a work climate in which people feel free to mention problems and to seek support2 ) . Longitudinal research recently showed full mediation of the stressor-strain link by perseverative thoughts and a bidirectional stressor-strain relation, i.e., impaired sleep quality predicts increase in work stressors36 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations